Simulation Sickness in Virtual Reality Games, How to Relieve it - Systematic Literature Study - Pereira, Milena Batalha; Lancelotte, Felipe da Silva; de Classe, Tadeu Moreira; Garcia, Ana Cristina Bicharra (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Immersive technologies have introduced innovative possibilities across various fields, including entertainment, sports, education, healthcare, training, and rehabilitation. Despite the increasing popularity and feasibility of these technologies, owing to their ability to create a heightened sense of presence, a significant challenge remains in the widespread adoption of virtual reality: simulation sickness, also known as cybersickness. This phenomenon manifests as symptoms such as nausea, dizziness, and fatigue, arising from factors like sensory discrepancies between real and virtual movements, latency, graphic quality, and individual susceptibility. This article aims to provide a comprehensive review of the current literature on cybersickness, exploring its causes and identifying methods to mitigate its adverse effects through advancements in hardware, software, and usability settings, ultimately striving for a more comfortable and positive virtual experience.